Assessment of Neck Imbalance in Adolescent Idiopathic Scoliosis Patients: A Cross‐Section Study Based on Body Image of 115 Patients with Main or Double Thoracic Curve. Issue 2 (23rd November 2022) - Zhang, Huawei; Wang, Ben; Wu, Aimin; Huang, Chongan; Pan, Xiangxiang; Chen, Boda; Ni, Libin; Shi, Yifeng; Meftah, Zaher Ali Mohamed; Wang, Xiangyang
Abstract : Objective: Neck imbalance negatively affects body aesthetics of adolescent idiopathic scoliosis (AIS) patients. The evaluation of neck imbalance is currently limited to radiographic parameters, but lacks visual indicators. Therefore, the purpose of this study was to establish indexes of neck imbalance based on body image and to investigate whether these indexes can truly reflect neck imbalance in AIS patients. Methods: We performed a cross‐sectional study at a single institution between June 2017 and September 2020 and there were 115 subjects involved in this research. All patients were diagnosed with adolescent idiopathic scoliosis, Lenke type I/II. Radiographic parameters measured included cervical axis tilt (CAT), T1 tilt, first rib angle (FRA), clavicle angle (CA), radiographic shoulder height (RSH), proximal thoracic curve (PTC), apical vertebra translation of proximal thoracic (AVT of PT), main thoracic curve (MTC), apical vertebra translation of main thoracic (AVT of MT) and coronal balance (CB/C7PL‐CSVL). Neck imbalance indexes were obtained and measured following a standardized manner. Intra‐class correlation coefficient (ICC) analysis was performed for neck imbalance indexes to determine their intra‐observer and inter‐observer reliability, and correlation tests were performed for neck imbalance indexes with the radiographic parameters mentioned above. Results: Strong intraobserver and interobserver reliability were observed in neck imbalance index (NII) 1 (0.91 and 0.88), neck imbalance index 2 (0.85 and 0.81) and NII 3 (0.82 and 0.80), P < 0.05. Significant correlation was found in cervical axis tilt ( R = 0.81 for NII 1, R = 0.77 for NII 2 and R = 0.78 for NII 3), T1 tilt ( R = 0.43 for NII 1, R = 0.52 for NII 2 and R = 0.48 for NII 3), first rib angle ( R = 0.41 for NII 1, R = 0.48 for NII 2 and R = 0.43 for NII 3), proximal thoracic curve ( R = 0.36 for NII 2) and apical vertebra translation of proximal thoracic ( R = −0.37 for NII 2 and R = −0.35 for NII 3) with neck imbalance indexes. Neck imbalance index 1 showed the highest correlation with cervical axis tilt ( R = 0.81, P < 0.01). Conclusions: Neck imbalance indexes established in our study were in good correlation with cervical axis tilt (CAT), At the meantime, they showed significant correlations with T1 tilt and first rib angle (FRA). Our study provides a practical method for measurement of neck imbalance regarding realistic perspective and makes up for the lack of photographic indexes about neck imbalance. Abstract : To help with the assessment of adolescent idiopathic scoliosis (AIS) patients' visual neck imbalance, we designed a set of new indexes based on body image of AIS patients.